Paideia Klemensa Aleksandryjskiego na przykładzie jego „Hymnu do Chrystusa Zbawiciela” - Heszen, Agnieszka (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2009)
'Hymnus to Christ' by Clement of Alexandria makes a poetic ending to the treatise 'paidagogos'. The hymn contains the conception of Christ as a teacher of the universe, a divine instructor. As the starting point of his deliberations, Clement takes Greek pagan culture within which the concept of paideia developed, and so to say, was promoted by Plato. Clement adopts paideia in its profound philosophical meaning that Plato gave it in his Laws defining God’s relation to the world as follows: ‘God is the Instructor of the whole world’. This very idea enabled Clement to depict Christ as the instructor of mankind. In my article, I focused on the hymn itself which crowns the treatise, as well as the synthesis of the idea of Christ Educator. The work has the qualities of a hymn of praise and thanksgiving and is an interesting example of the prayer poetry on the turn of 2nd century. Clement is one of the first Christian poets to draw on a rich source of Hellenic and classical culture, imitating the literary genres established in pagan Greece on one hand, and propagating Christianity on the other. The author is also regarded as the last and most important Christian Apologist. I think that all these aspects are reflected in 'Hymnus to Christ'. In my article, I carried out a stylistic, linguistic, metrical and theological analysis, and in the course of it, I pointed out the means and literary genre Clement used in order to depict Christ as an instructor and educator. Can Educator be acknowledged as a didactic work? I think that in the widest meaning of didactics understood as the education of mankind, that is, being an element of the philosophy of culture, as defined so by Clement himself, 'paidagogos' with its beautiful final chord can be regarded as a work on education, especially on the Educator.
Paideia by Clement of Alexandria on the Example of 'Hymnus to Christ'
Keywords: Clement of Alexandria; Christian poetry; Paideia; Litany; Educator